Criminal responsibility and profile of Turkish firesetters with schizophrenia - Balcioglu, Yasin Hasan (International journal of law, crime and justice, 2024)
This study aimed to examine a subgroup of Turkish firesetters diagnosed with schizophrenia spectrum disorders (SSD) for their motives, individual and offense-related characteristics and courses of action, and their association with expert assessment of criminal responsibility. A cohort of 50 arsonists with SSD, who underwent assessment for criminal responsibility by the Council of Forensic Medicine in Turkiye between 2009 and 2022, was analyzed using a comprehensive retrospective file review. Multivariate analyses indicated that being female, older, experiencing hallucinations at the time of the offense, having a primary diagnosis of SSD other than psychotic disorder not otherwise specified, and no prior convictions were associated with a higher likelihood of being found not criminally responsible. Singling out a definitive profile of SSD arsonists without criminal responsibility is challenging. Our findings, based on forensic expert assessments, suggest that positive psychotic symptoms and criminal history play crucial roles in determining criminal responsibility in this group.